Antibiotics release from cement spacers used for two‐stage treatment of implant‐associated infections after total joint arthroplasty. Issue 5 (12th October 2018) - Klinder, Annett; Zaatreh, Sarah; Ellenrieder, Martin; Redanz, Sylvio; Podbielski, Andreas; Reichel, Tobias; Bösebeck, Hans; Mittelmeier, Wolfram; Bader, Rainer
Abstract: Two‐stage revision arthroplasty is the treatment of choice for periprosthetic infection, a serious complication after knee or hip arthroplasty. Our prospective clinical trial aimed to investigate the concentrations of gentamicin and vancomycin in wound exudate and tissue in two‐stage revision arthroplasty. Wound exudate and periprosthetic membrane samples were collected from 18 patients (10 hip and eight knee patients), who were due for two‐stage treatment after a periprosthetic joint infection. Samples were taken during insertion of antibiotic‐impregnated spacers and after their removal. The concentrations of gentamicin and vancomycin in wound exudates and adjacent tissue were analyzed using high‐performance liquid chromatography mass spectrometry. Average time period of spacer implantation was 13.6 weeks (9.3–22.6 weeks). The concentration of vancomycin in wound exudate decreased from a median of 43.28 μg/mL (0.28–261.22) after implantation to 0.46 μg/mL (0.13–37.47) after the removal of the spacer. In the adjacent tissue, vancomycin concentration was mainly undetectable prior to spacer implantation (0.003 μg/g [0.003–0.261]) and increased to 0.318 μg/g [0.024–484.16] at the time of spacer removal. This was also observed for gentamicin in the tissue of patients who previously had cement‐free implants (0.008 μg/g [0.008–0.087] vs. 0.164 μg/g [0.048–71.75]) while in the tissue of patients with previously cemented prosthesis, baseline concentration was already high (8.451 μg/g [0.152–42.926]). Despite the rapid decrease in antibiotics release from spacer cement observed in vitro, in vivo antibiotics are much longer detectable, especially in the adjacent soft tissue. © 2018 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials Published By Wiley Periodicals, Inc. J Biomed Mater Res B Part B, 2019. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1587–1597, 2019.